2016
DOI: 10.1016/j.cbpb.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary tannic acid on the growth, hepatic gene expression, and antioxidant enzyme activity in Brandt's voles (Microtus brandti)

Abstract: This study was designed to investigate the physiological and biochemical responses of Brandt's voles to the persistent presence of dietary tannic acid. The diet for animals in the experimental group was supplemented with 3% dietary tannic acid for 5weeks. The control group received a commercial lab chow. No significant differences were detected in body weight, organ (heart, kidney, and liver) weights, and organ parameters between animals from two groups. However, voles in the experimental group had significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Therefore, certain doses of TA might enhance antioxidative defense and reduce oxidative stress in Brandt's voles. Similarly, CAT and GSH-Px activity increases in hepatic cell when adolescent Brandt's voles are treated with a TA diet for five weeks (Ye et al 2016). Furthermore, tannins in pomegranate juice were found to increase the plasma level of antioxidant enzymes (CAT and GSH-Px) in male rats (Türk et al 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, certain doses of TA might enhance antioxidative defense and reduce oxidative stress in Brandt's voles. Similarly, CAT and GSH-Px activity increases in hepatic cell when adolescent Brandt's voles are treated with a TA diet for five weeks (Ye et al 2016). Furthermore, tannins in pomegranate juice were found to increase the plasma level of antioxidant enzymes (CAT and GSH-Px) in male rats (Türk et al 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Drinking water containing TA for four weeks did not have any significant difference on body weight. Consistently, Brandt's voles supplemented with 3% TA in their diet for five weeks showed minimal variation in body weight to the control (Ye et al 2016). Feeding 3.3% TA in the diet of Brandt's voles also did not significantly change their body mass (Chen et al 2005b).…”
Section: Discussionmentioning
confidence: 94%
“…It noteworthy that TA as a polyphenolic compound exhibits anti-oxidative properties in animals. It has been demonstrated that TA strengthens the potential of antioxidant defense and is beneficial for the suppression of oxidative stress by increasing the activity of CAT and GSH-PX [20]. These polyphenols can behave as both antioxidants and pro-oxidants depending on the concentration and free radical source [11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is extremely urgent to seek effective and natural pollution-free alternatives like plant extracts as substitutes for antibiotics, zinc oxide, high copper, etc. Tannic acid (TA) is one of the typical representatives of high molecular weight polyphenol compounds that mainly exist in a wide variety of plants, such as plantderived feeds, grains, and fruits [4]. TA was usually considered as an anti-nutritional factor (ANF) in the past because it forms complexes with proteins, polysaccharides, digestive enzymes and metal ions, which are not conducive to the digestion and absorption of nutrients by animals and even considered to be toxic [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many medicinal plants with effect on mitigating diarrhea have revealed the presence of TA, like Gallnut contains massive TA, which even can reach 50-70% of its weight [9]. Subsequently, the anti-diarrhea, anti-oxidation, microbial homeostasis regulation and other effects of TA have been found one after another, which have attracted extensive attention of animal nutritionists [4,10].…”
Section: Introductionmentioning
confidence: 99%